ANALISIS PERBANDINGAN KINERJA KEUANGAN PROVINSI DI PULAU JAWA DAN PULAU KALIMANTAN TAHUN ANGGARAN 2024 - Naning Setiani; Aris Eddy Sarwono (Politeknik Negeri Ambon, 2025)
Introduction: This study analyzes the comparison of financial performance between provinces in Java and Kalimantan during the 2024 fiscal year. The aim of this research is to assess the level of fiscal dependency and the degree of fiscal decentralization as indicators of regional financial performance. Methods: This quantitative descriptive study uses secondary data obtained from the 2024 Budget Realization Reports (LRA) of eleven provinces, consisting of six from Java and five from Kalimantan. The analysis employs two financial ratios: the fiscal dependency ratio and the degree of fiscal decentralization. Results: The results show that provinces in Java exhibit lower fiscal dependency and higher fiscal decentralization compared to those in Kalimantan. Banten, DKI Jakarta, and West Java demonstrate the best financial performance, with dependency ratios below 30% and decentralization degrees above 70%. In contrast, provinces such as North Kalimantan and Central Kalimantan show dependency levels above 60% and decentralization degrees below 35%. These findings reflect a significant gap in fiscal independence between regions. In conclusion, increasing Local Own-Source Revenue (PAD) through local economic development and improved governance is crucial to enhancing fiscal autonomy in Kalimantan provinces. Keyword: Fiscal Decentralization, Fiscal Dependency, Financial Performance, And Regional Autonomy